STUDENT BUSINESS DYNAMIC: BALANCING STUDY AND BUSINESS - Andi Hajar; Zakiyah Febrina Alasta; Kayla Del Alinan (Media Inovasi Pendidikan dan Publikasi, 2026)
The phenomenon of students running side businesses is increasing in the digital economy era, but this poses challenges in maintaining a balance between academic and business responsibilities. This study aims to analyze the dynamics of role conflict, time management strategies, and the impact of business involvement on the academic performance of students at Universitas Negeri Makassar. The method used is descriptive qualitative with data collection techniques through in-depth interviews, questionnaires, observations, and literature studies. The results show that entrepreneur students, mostly in the third and fourth semesters, manage various businesses such as culinary and creative services, some of which have been started since elementary and junior high school. Field findings revealed that although students have structured schedules with a score of 4 out of 5, they still face the challenge of